Experience Report on the International Summer School of the “Post-Holocaust Remedies” Project - Rosenfeld, Julia; Reis, Finn Luis; Justus Liebig University Giessen (My University, 2024)
The aim of this experience report is to take an in-depth look at the events, results, and interpersonal interaction during the international Summer School as part of the “Post-Holocaust Remedies” Project.
Keywords: ddc:340